A Sociolinguistics Study on Gender in Egyptian Arabic Proverbs - Zainurrakhmah Zainurrakhmah (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
This study discusses gender in Egyptian Arabic proverbs from a sociolinguistic point of view to see the correlation between language and socio-cultural Egyptian society. The research method used in this study is a combination of intralingual, extra lingual, hermeneutic, and correlational methods. Based on the results of the analysis, it is known that gender disclosure in Egyptian Arabic proverbs uses lingual units in the form of words and phrases. As for the meaning, the expression of gender in Egyptian Arabic uses a literal or actual meaning and a figurative meaning or a non-true meaning. The gender gap that appears in Egyptian Arabic proverbs is in the form of relationship gaps, roles in the family, and the construction of stereotypes of women as inferior and dependent figures. The gender gap reflected in the proverb is in accordance with the reality of the high level of gender inequality in Egypt. This reveals that there is a correlation between language and socio-cultural Egyptian society.